Entheseal involvement in systemic lupus erythematosus: are we missing something?. (March 2017) - Di Matteo, A; Satulu, I; Di Carlo, M; Lato, V; Filippucci, E; Grassi, W
Background: Musculoskeletal involvement is extremely common in patients with systemic lupus erythematosus (SLE). Continuing the research initiated in patients with inflammatory arthritis, recent studies have shown the potential role of musculoskeletal ultrasound (MSUS) in the evaluation of clinical and subclinical lupus synovitis. The inflammatory process in SLE is traditionally considered to be localized at synovial tissue areas while enthesis is not included among the possible targets of the disease. Patients and methods: Entheses included in the Glasgow Ultrasound Enthesitis Scoring System were scanned in a cohort of 20 SLE patients serving as disease controls in an MSUS study aimed at assessing enthesitis in patients with psoriatic arthritis. We describe in detail four cases with unexpected and unequivocal expressions of MSUS enthesitis according to the OMERACT definition. Three out of four patients had no predisposing factors for enthesopathy. Case no. 2 was treated with a variable-dose prednisone regimen. Results: In the four cases MSUS examination revealed relevant grey-scale and power Doppler abnormalities at the entheseal level, most commonly at the distal insertion of the patellar tendon. Signs of clinical enthesitis were detected in only one patient. Conclusions: This case series shows for the first time the presence of clearly evident MSUS findings indicative of enthesitis in four out of 20 SLE patients (20%), raising the hypothesis that enthesis could be a missing target in the clinical evaluation of SLE patients. Our case series justifies further investigations for a better evaluation of the prevalence, characteristics and clinical relevance of entheseal involvement in SLE.